Бухгалтерский учет: учебник - Бакаев А. С. Александр Сергеевич; Безруких П. С. Петр Степанович; Врублевский Н. Д. Николай Дмитриевич; Ивашкевич В. Б. Виталий Борисович; Новодворский В. Д. Владимир Дмитриевич; Шеремет А. Д. Анатолий Данилович; Шнейдман Л. З. Леонид Зиновьевич (Библиотека журнала "Бухгалтерский учет")
Исключено из фонда НТБ ТПУ